Sharia Compliance On Rewards In Sharia Saving At BMT NU Ngasem - Salma Utiya Hikmah; Galuh Widitya Qomaro (International Conference on Islamic Economic (ICIE), 2022)
Wadi’ah Yad adh-Dhomanah is a conract for safekeeping of goods where the recipient of the deposit with or without the permission of the owner of the goods can take advantage of the goods that are deposited and must be responsible for the loss or damage of the goods. All profits obtained by the use of the goods become the right of the recipient of the deposit. This study aims to review the aspects of sharia compliance with the Wadi’ah Yad adh-Dhomanah contract and reward giving to savings products at BMT NU NGASEM. The sharia reference used in this study is the DSN MUI Fatwa NO. 86/DSNMUI/XII/2012 about rewards in Islamic Financial Institution Funds This is a descriptive qualitative research with interview data collection methods and documentation studies. The analysis tool uses a comparative approach. The results of the study found that the majority of Wadi’ah Yad adh-Dhomanah contracts and reward giving to savings products at BMT NU NGASEM have met sharia compliance but there are some points in giving reward s that are not in accordance with the rules of the DSN MUI Fatwa NO. 86/DSNMUI/XII/2012.